(untitled) (Research, Society and Development, 2020)
Introduction: Classically, thyroid nodules are initially evaluated by ultrasonography in Mode B. Despite being sensitive for the diagnosis of NT, it does not take into account the stiffness of the nodule, an important characteristic that is related to its malignancy. In this sense, elastography has been used as an instrument to assist in the diagnosis of thyroid nodules. With this in mind, the aim of the present study is to qualitatively assess the performance of manual pressure elastography in the differential diagnosis of malignant and benign thyroid nodules in adults. Method: This is a prospective, observational study, which included patients who had thyroid nodules and required fine needle aspiration (FNAB). The elastography was obtained in real time from the US in Mode B. The percentage of the nodule’s rigid area was calculated using the ImageJ software. Results: The study included 41 patients, 87.8% female. Age ranged from 18 to 75 years, with an average of 46.4 years (SD: 13.57). Most of the nodules were classified as TI-RADS 3, 53.7%. As for the Bethesda classification, 82.9% of the sample was classified as Bethesda 2 (benign nodule). The percentage of rigid area (% AR) ranged from 3% to 73%, with an average of 28.73% (SD: 18.15). Highly suspicious nodules from the TI-RADS classification had a higher AR% (51.6%). Regarding cytological analysis, nodules characterized as benign had an average AR% of 24.23% (SD: 13.66), while malignant ones of 55% (SD: 19.94), a difference of 30.77% , which proved to be statistically significant (p <0.001). Conclusion: The quantitative evaluation of Strain-type elastography based on the% AR evaluation proved to be useful to discriminate between benign and malignant nodules and is presented as a tool that can complement the assessment of thyroid nodules.